2009
DOI: 10.1186/1471-2202-10-55
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic relationship between brain structure and dynamics

Abstract: Background: Brain structure and dynamics are interdependent through processes such as activity-dependent neuroplasticity. In this study, we aim to theoretically examine this interdependence in a model of spontaneous cortical activity. To this end, we simulate spontaneous brain dynamics on structural connectivity networks, using coupled nonlinear maps. On slow time scales structural connectivity is gradually adjusted towards the resulting functional patterns via an unsupervised, activity-dependent rewiring rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(181 citation statements)
references
References 63 publications
7
174
0
Order By: Relevance
“…These observations confirmed that the relationship between FCS and rCBF was not solely the result of structural covariates. A growing number of empirical (6,29) and computational (30,31) studies support the hypothesis that spontaneous neural activity is shaped, but not limited, by the underlying anatomy. Our observations suggest that metabolic demands also have a close relationship with intrinsic functional organization of the brain networks.…”
Section: Discussionmentioning
confidence: 94%
“…These observations confirmed that the relationship between FCS and rCBF was not solely the result of structural covariates. A growing number of empirical (6,29) and computational (30,31) studies support the hypothesis that spontaneous neural activity is shaped, but not limited, by the underlying anatomy. Our observations suggest that metabolic demands also have a close relationship with intrinsic functional organization of the brain networks.…”
Section: Discussionmentioning
confidence: 94%
“…An alternative explanation is that these unusual pathways are the consequence of synesthetic experiences (Jancke et al 2009;Weiss and Fink 2009). Given that gray matter volume changes in the human adults' brain as a result of short periods of training have been demonstrated (Kwok et al 2011), and that brain dynamics are claimed to promote neuroanatomical self-organization (Rubinov et al 2009), the interpretation of synesthetic anatomical peculiarities as a result of repetitive intersensory coupling is not implausible. In this case, functional imbalance would be responsible for structural variations.…”
Section: The Canonical Regions Of Interestmentioning
confidence: 99%
“…Theoretical work has related these dynamics to the generation of a "community architecture" of brain networks (12). Communities are groups of interacting brain regions that are more tightly functionally related to each other than to the rest of the brain.…”
mentioning
confidence: 99%